Depressive rumination : nature, theory and treatment - Papageorgiou, Costas; Wells, Adrian (John Wiley, 2004)
Rumination (recyclic negative thinking), is now recognised as important in the development, maintenance and relapse of recurrence of depression. For instance, rumination has been found to elevate, perpetuate and exacerbate depressed mood, predict future episodes of depression, and delay recovery during cognitive therapy. Cognitive therapy is one of the most effective treatments for depression. However, depressive relapse and recurrence following cognitive therapy continue to be a significant problem. An understanding of the psychological processes which contribute to relapse and recur.